Hydrolysis of Diazonium Salts Using a Two‐Phase System (CPME and Water). Issue 6 (16th July 2015) - Taniguchi, Toshihide; Imoto, Mitsutaka; Takeda, Motonori; Nakai, Takeo; Mihara, Masatoshi; Iwai, Toshiyuki; Ito, Takatoshi; Mizuno, Takumi; Nomoto, Akihiro; Ogawa, Akiya
ABSTRACT: A new method for the hydrolysis of diazonium salts, without the formation of tar, was developed. A two‐phase system consisting of cyclopentyl methyl ether (CPME) and water is very effective for the hydrolysis of diazonium salts. Using this solvent system, the diazonium salt prepared from 3‐(4‐nitrophenoxy)aniline gave 3‐(4‐nitrophenoxy)phenol in high yield (96%) within 20 min. The synthesized phenol is an industrially important raw material in polymer syntheses. Furthermore, the use of the present two‐phase system of CPME and water successfully brought about the efficient conversions of several m‐substituted anilines into the corresponding m‐substituted phenols. This is the first example of hydrolysis of diazonium salts using the two‐phase system (CPME and water).